Tree communities rapidly alter soil microbial resistance and resilience to drought. (20th December 2014) - Rivest, David; Paquette, Alain; Shipley, Bill; Reich, Peter B.; Messier, Christian
Summary: The ability of soil microbial communities to withstand and recover from disturbance or stress is important for the functional stability of forest ecosystems. However, the relationship between the community responses of soil microbes and variation in tree mixtures vs functional composition remains poorly understood. We investigated soil biochemical properties and soil microbial resistance and resilience to drought in three 4‐year‐old tree monocultures ( Acer saccharum Marsh, Larix laricina (Duroi) K. Koch and Pinus strobus L.) and two tree species combinations ( L. laricina/A. saccharum and L. laricina/P. strobus ) planted in a high‐density tree field experiment located in southern Quebec, Canada. The experimentally imposed drought stress consisted of maintaining soil material for 30 days at 25% of water‐holding capacity (WHC). Microbial biomass was assessed immediately after the water stress (resistance) and 15 and 30 days following drought (resilience). Results showed that tree communities influenced soil chemistry, soil respirometry properties and microbial resistance and resilience. We measured significant non‐additive (i.e. both synergistic and antagonistic) effects of mixing tree species in some of the soil biochemical properties measured, mostly in the L. laricina/A. saccharum mixture. However, we did not find non‐additive effects of tree mixtures on microbial resistance and resilience. A structural equation modelling analysis revealed that resistance and resilience were mostly modulated by direct effects of community‐weighted means (CWM) of leaf litter lignin content and mineralizable N, and by indirect links from tree density and CWM of leaf litter N content via mineralizable N. This study suggests that tree species identity surpassed species mixtures as a key driver of soil microbial resistance and resilience. We showed a trade‐off between microbial resistance and resilience in soil food webs, which is consistent with ecological theory. Our results indicate that differences in functional traits between tree species may rapidly be reflected in divergent soil biochemical properties and that these differences can in turn drive soil microbial resistance and resilience to drought. Abstract : Lay Summary